A formação pré-serviço do professor de língua estrangeira em curso de licenciatura: crenças e reflexões em experiências de estágio supervisionado em diferentes contextos (sala de aula e teletandem) - Kaneoya, Marta Lúcia Cabrera Kfouri [UNESP] (My University, 2014)
This article aims to show the results of an institutional research in Applied Linguistics, which tries to comprehend how the initial teaching practice occurs in diversely figured contexts of foreign language teaching-learning (on-site and virtual), as well as how such contexts may mutually favor and encourage reflective and critical training of the language teacher in/for a contemporary world. It´s possible to notice a reflective attitude of four Brazilian foreign language (Spanish, English and Italian) teachers in initial training, especially regarding some aspects related to the teaching-learning languages process, such as roles of the participants; relevance of meaningful interaction; engaged cultures; teaching of a foreign language and mother tongue teaching as foreign one; teaching and learning typologically similar languages; constitution of the place to learn-teachIt´s possible to notice a reflective attitude of four Brazilian foreign language (English, Italian and Spanish) teachers in pre-service education, especially about some aspects of language teaching and learning process, such as the role of the participants; the relevance of significant interactions; the involved cultures; the teaching of a foreign language and the teaching of the mother tongue as a foreign language; the teaching of similar languages as Portuguese and Spanish; and the constitution of the place of teaching and learning languages. The results indicate that the experience of experiencing the dynamics of a conventional didactic context of language teaching (classroom), alongside to the experience of teaching and learning in a context of virtual educational settings (teletandem), it was especially important for the critical training of the future language teachers and to the awareness about the practice of teaching languages in times of technological innovation.

Este artigo tem por objetivo apresentar resultados de um projeto de pesquisa institucional em Linguística Aplicada, no qual se busca compreender como ocorre a prática inicial docente em contextos diversamente configurados de ensino/aprendizagem de língua estrangeira (presencial e virtual), bem como de que maneira esses contextos podem se favorecer mutuamente e favorecer a formação reflexiva e crítica do professor de línguas, em/para um mundo contemporâneo. É possível perceber a atitude reflexiva de quatro professores brasileiros de língua estrangeira (espanhol, inglês e italiano) em formação inicial, especialmente quanto a alguns aspectos relacionados ao processo de ensinar/aprender línguas, tais como papéis dos participantes; relevância da interação significativa; culturas envolvidas; ensino de uma língua estrangeira e ensino da língua materna como estrangeira; ensinar e aprender línguas tipologicamente próximas; constituição do lugar de aprender/ensinar. Os resultados indicam que a experiência de vivenciar a dinâmica de um contexto didático convencional de ensino de línguas (sala de aula), ao lado da experiência de ensinar e aprender em um contexto de configurações didáticas virtuais (teletandem), foi especialmente importante para a formação crítica dos futuros professores de línguas e para a conscientização sobre a prática de ensinar línguas em tempos de inovação tecnológica.
Pre-service training of foreign language teachers in licenciate course: beliefs and reflections on experiences of supervised traineeship in different contexts (classroom and teletandem)
Keywords: Formação de professores de línguas; ensino/aprendizagem de línguas; contextos presencial e virtual; language teacher training; languages teaching-learning; on-site and virtual contexts